Beyond the leiwah of eastern Arabia - (:unkn) unknown (My University, 2017)
Along the shores of the Persian Gulf and especially in Eastern Arabia, the leiwah is a possession rite involving music and dance. It is practiced by descendants of East African slaves named the Zunûj. They consider it as native from the Swahili coast (Bilâd as-sawâhil). Indeed, their presence in this region dates from the late nineteenth century as a result of the Indian Ocean Slave trade. However, the leiwah is known best as an entertaining dance and perceived by the young Arab urbanized generation as a secular and local tradition of Arabic inspiration. This situation is partly due to the fact that the presentation of this practice by the Gulf States cultural institutions minimize all its links to Africa and do not mention the history of the Zunûj slavery. What, then, does leiwah mean for those who practice it? What are the cultural influences on which it was established, as well as the specificities of this practice in Eastern Arabia, given that the old generation of the Zunûj considers the leiwah as an East African cultural expression and it is basically a rite of possession? This article focuses on the study of the leiwah in a diachronic perspective. The purpose being, on one hand, to replace in a historical perspective some anthropological and musicological elements observed in synchrony, and on the other, to clarify its cultural influences that would contribute to a better understanding of how and from what this practice was elaborated in Eastern Arabia.
Keywords: African Research